Effects of substituent position on aminobenzoate relaxation pathways in solution. Issue 40 (11th October 2021) - Rodrigues, Natércia d. N.; Woolley, Jack M.; Krokidi, Konstantina M.; Tesa-Serrate, Maria A.; Turner, Matthew A. P.; Hine, Nicholas D. M.; Stavros, Vasilios G.
Abstract : Transient absorption spectroscopy reveals the excited state dynamics of meta - and para -methyl anthranilate in solution. Implicit solvent computational methods insufficiently model these systems's behaviour, implying the need for explicit solvent models. Abstract : The negative effects of ultraviolet radiation (UVR) on human skin have led to the widespread use of sunscreens, i.e. skincare products containing UV filters to absorb, reflect or otherwise block UVR. The mechanisms by which UV filters dissipate energy following photoexcitation, i.e. their photodynamics, can crucially determine a molecule's performance as a sunscreen UV filter. In this work, we evaluate the effects of substituent position on the in-solution relaxation pathways of two derivates of methyl anthranilate (an ortho compound that is a precursor to the UV filter meradimate), meta - and para -methyl anthranilate, m -MA and p -MA, respectively. The photodynamics of m -MA were found to be sensitive to solvent polarity: its emission spectra show larger Stokes shifts with increasing polarity, and both the fluorescence quantum yield and lifetimes for m -MA increase in polar solvents. While the Stokes shifts for p -MA are much milder and more independent of solvent environment than those of m -MA, we find its fluorescence quantum yields to be sensitive not only to solvent polarity but to the hydrogen bonding character of the solvent. In both cases ( m - and p -MA) we have found common computational methods to be insufficient to appropriately model the observed spectroscopic data, likely due to an inability to account for explicit solvent interactions, a known challenge in computational chemistry. Therefore, apart from providing insight into the photodynamics of anthranilate derivatives, the work presented here also provides a case study that may be of use to theoretical chemists looking to improve and develop explicit solvent computational methods.